The Universal Epitope of Influenza A Viral Neuraminidase Fundamentally Contributes to Enzyme Activity and Viral Replication - Doyle, Tracey M. (American Society for Biochemistry and Molecular Biology, 2013)
The only universally conserved sequence among all influenza A viral neuraminidases is located between amino acids 222 and 230. However, the potential roles of these amino acids remain largely unknown. Through an array of experimental approaches including mutagenesis, reverse genetics, and growth kinetics, we found that this sequence could markedly affect viral replication. Additional experiments revealed that enzymes with mutations in this region demonstrated substantially decreased catalytic activity, substrate binding, and thermostability. Consistent with viral replication analyses and enzymatic studies, protein modeling suggests that these amino acids could either directly bind to the substrate or contribute to the formation of the active site in the enzyme. Collectively, these findings reveal the essential role of this unique region in enzyme function and viral growth, which provides the basis for evaluating the validity of this sequence as a potential target for antiviral intervention and vaccine development.